Herramientas educativas para el desarrollo de la percepción visual en niños del Nivel Inicial 1 del Centro de Educación Inicial “República de Guatemala”, de la ciudad de Quito, provincia de Pichincha. - Loja Carvajal, Joselyn Carolina (2023)
The current study, "Educational Tools for the Development of Visual Perception in children of pre-kindergarten at República de Guatemala pre-school, located in Quito, Pichincha province, is motivated by the need to strengthen the teaching and learning process. Specifically, this project's goal is to analyze those educational tools that are beneficial to the development of the visual perception. The study is basic and field-based and includes a design that is descriptive and not experimental. Its study sample consists of 16 children between male and female. Likewise, for data processing, the observation technique was applied, using the observation sheet as a research instrument, and then analyzing and interpreting the results, in order to verify the proposed objectives and establish convincing conclusions, from which it was emphasized that through the use and application of educational tools, the development of visual perception in children can be enhanced, Consequently, it is necessary to promote in teachers a constant training on physical, didactic, digital or virtual educational tools, since they are a key point in the development of visual perception, since society is in constant change and with it the needs and interests of those who make it up.